ANALYTICAL PRESENTATION OF THE 2020 NATIONAL CORE CURRICULUM IN HUNGARY - Pál HAMAR; István SOÓS (Cluj University Press, 2022)
The Physical Education and Health Development learning area of the National Core Curriculum (NCC) 2020 and the framework curricula that form a coherent unit with it includes a set of goals and contents that meet the challenges of the 21st century. One of the prominent components of the 21st century image of man is that the individual is active, but at the same time, capable of reflective deliberation. A person of action is characterized by the right attitudes related to movement, a physically active lifestyle, realistic self-acceptance, autonomy combined with social responsibility, openness to innovative initiatives and the ability to apply reliable solutions. A physically and mentally healthy person experiences the state of health and a harmonious life as a value. The abilities and skills related to movement as a basic competence, as well as the motor abilities and skills that are mobilized according to the given situation, are the basis for the individual to become an active member of society, and are characterized by safety in movement throughout life. A significant positive of NCC 2020 is that, in addition to speaking, reading, writing, text comprehension, orientation to quantitative, spatial-visual and temporal conditions, movement is also found among the basic competencies. There are learning areas (subjects) in NCC 2020, in the following system: Hungarian language and literature (literature, Hungarian language); Mathematics (mathematics); History and civic knowledge (history, civic knowledge, country and people knowledge); Ethics/faith and morality; Natural science and geography (environmental knowledge, natural science, integrated natural science, biology, chemistry, physics, geography); Foreign language (first and second foreign language); Arts (singing and music, drama and theatre, visual culture, motion picture culture and media literacy); Technology (technique and design, digital culture); Physical education and health promotion (physical education); Community education (class head teacher's lesson). The learning area of NCC 2020 Physical Education and Health promotion follows the following structure: first, the general principles and goals of the learning area and the physical education subject are formulated; after that, specific characteristics of the teaching of the subject can be found in chapters 1-4 and 5-8 and 9-12 projected by grade; the next point contains the main topics, also divided into four grades. In the NCC, certain characteristics of physical education learning and teaching are also presented by education stage. The educational process takes place along seven development areas: movement culture development; motor abilities development; development of motor skills - learning to move; games; contests, competitions; prevention, lifestyle; healthy physical development, health promotion. These development areas are closely aligned with the main topics of the subject, as well as with the learning outcomes (general requirements) set as overall goals and related to the development areas.